The Resuscitation of Apparently Stillborn Neonates: A Peek Into the Practice in China - Chen, Xueyu; Li, Huitao; Song, Jingyu; Sun, Panpan; Lin, Binchun; Zhao, Jie; Yang, Chuanzhong (Frontiers in Pediatrics, 2020)
Apparent stillbirth is defined as a neonate born in a stage of secondary apnoea and hardly responds to basic resuscitation procedures proposed by the Neonatal Resuscitation Program (NRP). Mounting experimental and clinical evidence shows that stringently adhering to the NRP guidelines may delay sufficient ventilation and chest compressions and consequently prolong the duration of asystole in apparently stillborn neonates. To add to this field, we summarized our experience with the resuscitation of apparently stillborn neonates and reported the neonatal outcomes of a cohort of apparently stillborn neonates resuscitated at a tertiary care centre in China.